A helping hand with language learning: teaching French vocabulary with gesture. Issue 2 (2nd April 2016) - Porter, Alison
Abstract : Finding ways to make language teaching practices both active and effective is of great importance for young learners. However, extending the foreign language production of young learners in instructional settings beyond the naming of objects is often challenging. The memorisation abilities of very young learners (children aged 5–7) sometimes appear limited and attrition is a major issue, given the once-weekly teaching sessions which are a common model for UK primary modern foreign language instruction. This study explored the effectiveness of gestures, as a form of elaborated encoding for young learners, in aiding target language memorisation and slowing attrition through the implementation of a strict teaching protocol and a bespoke pedagogical tool. Findings show significant advantage for short-term retention of a story told with both gestures and pictures when compared with a story told with pictures only. Delayed post-test scores for the gestured story demonstrate a greater rate of attrition from a higher initial mean score than the non-gestured story. This study will therefore assert that gestures boost memorisation due to retrieval cues and richer memory traces. However, it will also note that, when considering longer-term retention, a higher rate of attrition for the gestured story shows that a richer trace alone is not enough. In other words, whilst elaborated processing enhances memorisation, even richer traces need refreshing through repetition and retrieval practice.